(untitled) (Journal of Economic Research & Business Administration, 2016)
The transition to a market economy, economic reforms suggest that in many programs is not enough little place is the question of innovation as a means and incentive to entrepreneurship. Meanwhile, the reform of prop- erty relations, privatization and privatization are responsible for the growth of the diversity of farming, ways of organizing economic life. According to the generally accepted in the domestic science, the result of innovative approach of the company may be new ideas, new or improved products or processes, new forms and methods of organization and management. A special place in the aggregate of these results takes intellectual property, whose objects are the creations of the human mind, his intellect.